Metropolitan planning and development in Boston and its environs. 1922 Boston Chamber of commerce, Committee on municipal and metropolitan affairs, Committee on public utilities. - Boston Chamber of Commerce. (Tufts University. Tisch Library., 2015)
1 online resource (32 pages) illustrations.; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.